Potential Simultaneous Inhibitors of Angiotensin-Converting Enzyme 2 and Transmembrane Protease, Serine 2 - Wu, Ching-Yuan; Lin, Yu-Shih; Yang, Yao-Hsu; Shu, Li-Hsin; Cheng, Yu-Ching; Liu, Hung Te (Frontiers in Pharmacology, 2020)
Outbreak of coronavirus disease 2019 (COVID-19) occurred in Wuhan and has rapidly spread to almost all parts of world. GB-1, the herbal formula from Tian Shang Sheng Mu of Chiayi Puzi Peitian Temple, is used for the prophylaxis of SARS-CoV-2 in Taiwan. In this study, we investigated that the effect of GB-1 and the index compounds of GB-1 on the ACE2 and TMPRSS2 expression through in vitro and in vivo study. In our result, GB-1 can inhibit ACE2 and TMPRSS2 protein expression in HepG2 cells, 293T cells and Caco-2 cells without cytotoxicity. For the mouse model, GB-1 treatment could decrease ACE2 and TMPRSS2 expression levels of lung and kidney tissue without adverse effects, including nephrotoxicity and hepatotoxicity. In the compositions of GB-1, 0.5-1 mg/ml of glycyrrhiza uralensis Fisch. ex DC. extract could not inhibit ACE2 mRNA and protein expression in HepG2 cells. In addition, theaflavin 3-gallate could inhibit protein expression of ACE2 and TMPRSS2 without significant cytotoxicity. Our results suggest that GB-1 and theaflavin 3-gallate could act as potential candidates for prophylaxis or treatment of SARS-CoV-2 infection through inhibiting protein expression of ACE2 and TMPRSS2 for the further study.